3x-y=5, x-4y =-2

5x+4y-2/2y+3

3x+4y=-2...(1)

x=2y...(2)

put the value of x from eq. (2) to eq.(1)

3*(2y)+4y=-2

6y+4y=-2

10y=-2

y=-1/5

put the value of y into eq.(2)

x=2*(-1/5)

x=-2/5

values are : X=-2/5 and y=-1/5

x=2y...(2)

put the value of x from eq. (2) to eq.(1)

3*(2y)+4y=-2

6y+4y=-2

10y=-2

y=-1/5

put the value of y into eq.(2)

x=2*(-1/5)

x=-2/5

values are : X=-2/5 and y=-1/5

There are two equations in the problem;

3x+4y=-2x, 3x+4y=2y

There are two variables in the problem x and y so we would have to take a variable´s value from one equation,

3x+4y=-2x

3x+2x+4y-4y=-2x+2x-4y

5x=-4y

x=-4y/5

Putting the value of x in second equation;

3x+4y=2y

3(-4y/5)+4y-4y=2y-4y

12y/5=-2y

12y/5+2y=-2y+2y

taking LCM

(12y+10y)/5=0

22y/5 x 5=0x5

22y=0

22y/22=0/22

y=0

Putting the value of y in first equation

x=-4y/5

x=-4(0)/5

x=0

so, x=0 and y=0 or (x,y)=(0,0)

3x+4y=-2x, 3x+4y=2y

There are two variables in the problem x and y so we would have to take a variable´s value from one equation,

3x+4y=-2x

3x+2x+4y-4y=-2x+2x-4y

5x=-4y

x=-4y/5

Putting the value of x in second equation;

3x+4y=2y

3(-4y/5)+4y-4y=2y-4y

12y/5=-2y

12y/5+2y=-2y+2y

taking LCM

(12y+10y)/5=0

22y/5 x 5=0x5

22y=0

22y/22=0/22

y=0

Putting the value of y in first equation

x=-4y/5

x=-4(0)/5

x=0

so, x=0 and y=0 or (x,y)=(0,0)

2x-2y=-14

4x-y=22

the solution is

4x-y=22

the solution is

X+4y=-2

4x-2y=-10

4x-2y=-10